2000
DOI: 10.1046/j.1365-313x.2000.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Monosaccharide/proton symporter AtSTP1 plays a major role in uptake and response of Arabidopsis seeds and seedlings to sugars

Abstract: The aim of this study was to investigate the in vivo properties and function of the high-affinity monosaccharide/proton symporter AtSTP1 of Arabidopsis. We isolated an Atstp1 knock-out mutant and found that this plant grows and develops normally. The AtSTP1 gene is expressed in germinating seeds and seedlings, with AtSTP1 activity found mainly in the seedling root. The rate of uptake of [(14)C]-3-O-methylglucose and [(14)C]-D-glucose is 60% less in Atstp1 seedlings than in the wild type, showing that AtSTP1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 39 publications
6
56
0
1
Order By: Relevance
“…Our data showed that monosaccharide transport activity in Arabidopsis roots changed under conditions of high salinity as a result of changes in the expression level of transporter genes. It has been reported previously that STP1 is involved in the uptake of monosaccharides from the surrounding environment (11). In the present study we demonstrated that STP13 also plays an important role in the uptake of monosaccharides in Arabidopsis roots.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our data showed that monosaccharide transport activity in Arabidopsis roots changed under conditions of high salinity as a result of changes in the expression level of transporter genes. It has been reported previously that STP1 is involved in the uptake of monosaccharides from the surrounding environment (11). In the present study we demonstrated that STP13 also plays an important role in the uptake of monosaccharides in Arabidopsis roots.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, mannose strongly inhibits seed germination and postgermination growth (27). It has been previously reported that the stp1 mutant exhibits insensitivity to galactose and mannose (11). We also observed that the root lengths of the stp1 mutants were longer than those of wild type plants under high galactose conditions (Fig.…”
Section: The Absorption Of Monosaccharides From the Surroundingsupporting
confidence: 71%
See 1 more Smart Citation
“…Arabidopsis thaliana seeds were surface-sterilized, stratified, and germinated as described previously (Sherson et al, 2000). Seedlings were grown on half-strength MS medium (Sigma-Aldrich, Poole, Dorset, UK) with or without sucrose in continuous light (100 mmolÁm ÿ2 Ás ÿ1 ) at 228C unless otherwise stated.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…The gene-specific primers MS50 (5Ј-ATG GAG CTC GAG ACC TCA GTT TAT C-3Ј), MS51 (5Ј-GCT GCT TTC GAG GAC GCT TTG TCT C-3Ј), MS30 (5Ј-GAG CCT TGA GAC ATT GAT AGG GTA G-3Ј), and MS31 (5Ј-ACA AGT ACG GAT GAG AAG ATC AGA G-3Ј) were used in combination with T-DNA left border primers (13,15,16). This screening identified an insertion in a plant in the Wassilewskija ecotype from the Versailles collection (15,16).…”
Section: Screening Of T-dna Insertion Lines and Isolation Of Mls Knocmentioning
confidence: 99%